A Study of the Effects of Kokoro Alate, A Crisis Resolution Programme of Agidigbo 88.7 FM Radio Station on the People of Akinyele Local Government of Oyo State - Abdullahi, Shehu Abdulkadir; Olanase, Sarah Oluwadamilola (ALSYSTECH Journal of Education Technology, 2025)
This research was conducted to evaluate the effectiveness of Kokoro Alate, a crisis resolution programme on Agidigbo 88.7FM radio station, in promoting community resilience and mitigating crises in Akinyele Local Government, Oyo State.The research aimed to examine the programme's influence on listeners' perceptions and attitudes towards crisis, its effectiveness in promoting community resilience, and the challenges and opportunities associated with its implementation. A descriptive survey method was employed, targeting, 80 adults ( 50 unmarried and 30 married) selected through simple random sampling from Ajibode, Akinyele Local Governmen The study revealed that crisis management radio programs significantly influence listeners' perceptions and attitudes towards crisis, with education being the most impactful aspect. Kokoro Alate has educated a large number of people on how to conduct themselves during crises and resolve disputes. However, despite awareness of the importance of feedback, respondents hesitated to contribute, limiting the programme's effectiveness. The study concludes that crisis resolution programmes like Kokoro Alate are vital tools for combating social crises. To enhance programme effectiveness, awareness campaigns on crisis resolution programmes should be conducted.Further research is recommended to investigate reasons for low feedback and declining radio audiences. Additionally, government and private broadcasts should prioritize crisis-resolution programming. By addressing these areas, Kokoro Alate's influence can expand, enhancing community resilience and crisis management in Akinyele Local Government.